Efficient Consumption of Revenues from Natural Resources - an Application to Norwegian Petroleum Revenues - Q. Farooq Akram (Norges Bank, 2005)
This paper addresses the so-called natural resource curse by devising a rule that can reduce macroeconomic costs associated with the consumption of revenues from natural resources. It assumes that such macroeconomic costs are mainly brought about by changes in the real exchange rate, which adjusts in order to maintain external balance. Thus it derives a consumption rule, denoted as the efficient consumption rate, that would make the behaviour of the real exchange rate mimic that of the real exchange rate in the absence of natural resources. Accordingly, growth of exports and imports of traditional goods and services, and implicitly the sectoral composition of the economy, become largely immune to the consumption of natural resources. The theoretical framework is applied to estimate and evaluate an efficient consumption rate for Norway's sizeable petroleum revenues.
hdl:11250/2498444
Keywords: Q38; F17; F41; F47; 330; Dutch disease; natural resources; real exchange rate